Update on the SNG001 drug, an INFβ therapy for COVID-19 - Holgate, Stephen (Henry Stewart Talks, 2020)
An overview of SNG001 therapy, Findings of the phase 2 clinical trial, Treatment potential at different stages of the disease, Advantages of the treatment delivery mode and accessibility, Potential use as a prophylaxis treatment, Follow up clinical trials to be undertaken, Other treatment settings for INFβ, For additional information please refer to the publication of Monk et al., The Lancet, November 12, 2020, DOI: https://doi.org/10.1016/S2213-2600(20)30511-7